Neural recordings can differentiate between spontaneously metastasizing melanomas and melanomas with low metastatic potential. - Jay Shiralkar; Tiana Anthony; Grant A McCallum; Dominique M Durand (PLoS ONE)
Multiple studies report that melanomas are innervated tumors with sensory and sympathetic fibers where these neural fibers play crucial functional roles in tumor growth and metastasis with branch specificity. Yet there is no study which reports the direct neural recording and its pattern during in-vivo progression of the cancer. We performed daily neural recordings from male and female mice bearing orthotopic metastasizing- melanomas and melanomas with low metastatic poential, derived from B16-F10 and B16-F1 cells, respectively. Further, to explore the origins of neural activity, 6-Hydroxidopamine mediated chemical sympathectomy was performed followed by daily microneurographic recordings. We also performed the daily bioluminescent imaging to track in vivo growth of primary tumors and distant metastasis to the cranial area. Our results show that metastasizing tumors display high levels of neural activity while tumors with low metastatic potential lack it indicating that the presence of neural activity is linked to the metastasizing potential of the tumors. Moreover, the neural activity is not continuous over the tumor progression and has a sex-specific temporal patterns where males have two peaks of high neural activity while females show a single peak. The neural peak activity originated in peripheral sympathetic nerves as sympathectomy completely eliminated the peak activity in both sexes. Peak activities were highly correlated with the distant metastasis in both sexes. These results show that sympathetic neural activity is crucially involved in tumor metastasis and has sex-specific role in malignancy initiation.